Development of the system for vibration diagnosis of bearing assemblies using an analog interface - Dovhan, Vasyl; Kvasnikov, Vladimir; Ornatskiy, Dmitro (Eastern-European Journal of Enterprise Technologies, 2018)
We have proposed a system for early vibration diagnosis of gas-pumping units, specifically bearing assemblies with improved metrological characteristics. The technique makes it possible to solve the task of early diagnosis of roller bearings under adverse conditions of application. The study has shown that this is achieved through the use of tracking notch filters based on N-channel structures using the iterative-integrating converters. The simulation results of the 4-channel filter under actual input signals of bearing damage have demonstrated its effectiveness. Based on this, we have built the resulting model for the filter’s output signal. Here we show a functional circuit for the root-mean-square values detector with a model of the output signal from the tracking notch filter at actual input signals. To build a model of signal at the input to a root-mean-square values detector, we determined filter responses for each frequency, which is responsible for a certain damage. The time of analysis was selected so that it was equal to a period of the minimum beat frequency, that is, Ta=164 ms (for a bearing of type 222). We investigated effectiveness of the device by simulating a damage to an actual gas turbine engine’s bearing. The procedure for analysis has been proposed and the generalized vibro-diagnostic criterion has been suggested, which takes into consideration the degree of engine’s load. This improves accuracy and reliability of preliminary analysis when diagnosing a roller bearing at the stage of the origin of the damage. Characteristics are given for the electrometric measuring amplifier for work with piezoelectric sensors and the proposed charge measuring amplifier to work with piezoelectric sensors. Under condition for the imbalance of the input link, which is due to the non-identity of parasitic capacitances of the input cable. It is shown that the penetration of a network disturbance to the output of the charge measuring amplifier provides for the signal/noise ratio that is two orders of magnitude better than that for the electrometric measuring amplifier.